2021
DOI: 10.1007/s00455-021-10338-9
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Neurogenic Dysphagia

Abstract: Autoimmune neurogenic dysphagia refers to manifestation of dysphagia due to autoimmune diseases affecting muscle, neuromuscular junction, nerves, roots, brainstem, or cortex. Dysphagia is either part of the evolving clinical symptomatology of an underlying neurological autoimmunity or occurs as a sole manifestation, acutely or insidiously. This opinion article reviews the autoimmune neurological causes of dysphagia, highlights clinical clues and laboratory testing that facilitate early diagnosis, especially wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 155 publications
0
16
0
Order By: Relevance
“…4 It is estimated to be quite common in OM (in around 26% of patients), 5 but it is much milder than in other types of IIM. 6 Inflammatory involvement of the swallowing muscles causes dysphagia in IIM, and dysphagia is estimated to present as an initial symptom in less than 10% of OM cases. 4 It can lead to severe complications such as weight loss or aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…4 It is estimated to be quite common in OM (in around 26% of patients), 5 but it is much milder than in other types of IIM. 6 Inflammatory involvement of the swallowing muscles causes dysphagia in IIM, and dysphagia is estimated to present as an initial symptom in less than 10% of OM cases. 4 It can lead to severe complications such as weight loss or aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions in the medullary structure can lead to the pressure of UES, which should be decreased when swallowing, increased (21). According to the literature reported, NMOSD with MO involvement was more likely to have dysphagia (6)(7)(8)(9). Hence, with the MO involvement may influence the CPG and NTS, and then lead to the higher UES residue pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study indicated that dysphagia frequently occurs in NMOSD with MO involvement ( 6 8 ), which can be detected through questionnaires and instrumental examination ( 7 , 8 ). Also oropharyngeal swallowing disorder might lead to the pneumonia and disability ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neurogenic dysphagia in these patients is also common and underappreciated. 59 Patients with stiff person spectrum disorders have a higher incidence of diabetes, so screening for hyperglycemia is important (especially when administering corticosteroids or glucose-containing IVIg) (CASE 7-4). patients, investigating and treating occult atypical causes of infection (eg, varicella-zoster virus, HSV) is crucial.…”
Section: Key Pointsmentioning
confidence: 99%
“…Physical therapy combined with long-acting benzodiazepines and other muscle relaxers (eg, baclofen, tizanidine) and focal botulinum therapy can provide tremendous symptomatic relief, but refractory cases or those with prominent functional burden should be considered for immunotherapies (eg, corticosteroids, intravenous immunoglobulin [IVIg], plasma exchange, rituximab, mycophenolate, cyclophosphamide, methotrexate, stem cell transplant). Neurogenic dysphagia in these patients is also common and underappreciated 59 . Patients with stiff person spectrum disorders have a higher incidence of diabetes, so screening for hyperglycemia is important (especially when administering corticosteroids or glucose-containing IVIg) ( case 7-4 ) 36,49 …”
Section: Stiff Person Syndromementioning
confidence: 99%